THE INFLUENCE OF COOPERATIVE MODEL AND INTRAPERSONAL INTELLIGENCE ON SOCIAL SKILL IN SOCIAL SCIENCE LEARNING FOR STUDENT (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The aim of the research is to determine the relationship among Cooperative Model and Intrapersonal Intelligence about Social Skills in Social Studies Learning for Students of grade 4 students in the state elementary school of Cipinang Melayu 09, East Jakarta, the amount of students are 68 students. The method used in writing is a quantitative method. The technique used to analyze the data is the statistical techniques of correlation and regression. The research result showed: 1) There is a significant difference between the social skills of the group of students who study with the CORE model and the social skills of the group of students who study with the TGT model. 2) There is a significant interaction between learning models, intrapersonal intelligence on social skills. 3) Social skills for students who have high intrapersonal intelligence and learn with the CORE model higher than students who study with the TGT model. 4) Social skills for students who have low intrapersonal intelligence and learning with the TGT model is higher than students who study with the CORE model.